北硫黄島の外来ネズミ類調査 - 飴田 洋祐; 川上 和人; 佐々木 哲朗; 堀越 宙 (東京都立大学小笠原研究委員会, 2021)
北硫黄島では、これまでクマネズミおよびドブネズミの生息が確認されている。本調査では、北硫黄島におけるネズミ類の生息現況を明らかにするため、センサーカメラによる自動撮影調査、誘引罠による捕獲調査を行った。その結果、海岸部から山頂近くまで広く生息していることが確認され、製糖工場(標高190m)においては1個体のクマネズミが捕獲された。また、踏査ルート上ではクマネズミの生体、食痕および糞が多数観察された。 On Kita-iwoto Island, the absence of Rattus rattus (Asian rat) and R. noorvegicus has been reported. Trail camera trapping and capture trapping were set up to clarify the current status of alien rats. As a result, rats have wide habitat between coast and the summit. An individual of Rattus rattus was captured at Seitokojo (elevation of 190m). Along the survey route, traces of alien rats (living, excrement and food marks) were observed frequently.